132k views
23 votes
M=p/n+4 make n the subject​

User Ulkas
by
5.0k points

2 Answers

11 votes

Answer:


m = (p)/((n + 4)) \\ (n + 4)m = p \\ nm + 4m = p \\ nm = p - 4m \\ n = (p - 4m)/(m) \\ n =( (p)/(m) - 4)

n=p/m-4 is the right answer.

User Rohit Dhawan
by
4.9k points
14 votes

Answer:


n = \frac {p - 4m}{m}

Explanation:

Given the algebraic expression;


m = \frac {p}{n + 4}

To make n the subject of formula.

Cross-multiplying, we have;


m*(n+4) = p


mn + 4m = p

Rearranging the equation, we have;


mn = p - 4m


n = \frac {p - 4m}{m}

User Wmakley
by
4.5k points